2016
DOI: 10.1182/blood-2015-09-670208
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor–dependent enrichment of a megakaryocytic precursor with a high potential to produce proplatelets

Abstract: International audienceThe mechanisms regulating megakaryopoiesis and platelet production (thrombopoiesis) are still incompletely understood. Identification of a progenitor with enhanced thrombopoietic capacity would be useful to decipher these mechanisms and to improve our capacity to produce platelets in vitro. Differentiation of peripheral blood CD34(+) cells in the presence of bone marrow-human mesenchymal stromal cells (MSC) enhanced the production of proplatelet-bearing megakaryocytes (MK) and platelet-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 29 publications
6
74
0
5
Order By: Relevance
“…23 We confirmed that StemRegenin 1 increases the number of platelets from imMKCLs when cultured with TA-316 (data not shown). Thus, TA-316 could be applied in combination with other small molecule modulators that function independent of the TPO/c-MPL signal.…”
Section: Discussionsupporting
confidence: 74%
“…23 We confirmed that StemRegenin 1 increases the number of platelets from imMKCLs when cultured with TA-316 (data not shown). Thus, TA-316 could be applied in combination with other small molecule modulators that function independent of the TPO/c-MPL signal.…”
Section: Discussionsupporting
confidence: 74%
“…Some studies suggest that contact with stromal cell precursors negatively controls megakaryocytic differentiation of the human hematopoietic cell line K562 3,4 or human CD34 progenitors, 5,6 whereas other studies suggest that stromal cells support or enhance megakaryopoiesis. [7][8][9] This apparent contradiction may reside in differences in experimental design and in the complexity of the processes involved in the generation of megakaryocytes (MKs) from HSCs. Indeed, MKs are generated from HSCs through multiple steps of committed MK progenitors, including a bipotent megakaryocytic erythroid progenitor (MEP), leading to the production of a unipotent MK precursor, which will then mature into large polyploid MKs that will extend proplatelets in the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are planned based on infusion of the expanded unit only. Recent in vitro studies [153] indicate that SR 1 promotes the production of megakaryocyte precursors from CD34+ cells with 90% reaching the proplatelet stage with TPO addition, thereby potentially contributing to the ex vivo production of platelets from normal cells for transfusion.…”
Section: IVmentioning
confidence: 99%